LITERASI DIGITAL DAN PENCARIAN LITERATUR PADA MAHASISWA KEDOKTERAN: DIGITAL LITERACY AND LITERATURE SEARCHING IN MEDICAL STUDENTS - Lestari, Ira Cinta; Diba, Farah; Darungan, Tezar Samekto; Nasution, Halimah Thania; Akbar, Surya; Azizah, Nur; Pulungan, Rizky Luly Ya Fatwa; Damanik, Rosa Zorayatamin (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Medical students need digital literacy and literature searching skills to support evidence-based learning. These competencies are essential for navigating scientific information and making accurate clinical decisions. The objective of this study is to review recent studies on the level of digital literacy and literature searching abilities among medical students and evaluate relevant educational interventions. A literature review was conducted using publications from 2016 to 2025, retrieved from PubMed, Scopus, and Google Scholar. Included studies were relevant to medical education and available in full text. Although students are accustomed to using digital technologies, many still lack adequate skills to search and evaluate scientific literature. Effective interventions include information literacy training, curriculum integration, and simulation-based learning. Digital literacy also influences students’ self-efficacy and mental well-being. Digital literacy and literature searching skills should be systematically integrated into medical education. Strengthening the curriculum in these areas prepares students to face challenges in the digital and technological landscape of modern medicine. AbstrakMahasiswa kedokteran perlu memiliki literasi digital dan keterampilan penelusuran literatur untuk mendukung pembelajaran berbasis bukti. Kemampuan ini penting dalam menavigasi informasi ilmiah dan mengambil keputusan klinis secara tepat. Penelitian memiliki tujuan untuk menelaah studi terbaru mengenai tingkat literasi digital dan kemampuan pencarian literatur pada mahasiswa kedokteran, serta mengevaluasi intervensi pendidikan yang relevan. Telaah pustaka dilakukan terhadap publikasi 2016–2025 dari database PubMed, Scopus, dan Google Scholar. Studi yang dipilih relevan dengan konteks pendidikan kedokteran dan tersedia dalam teks lengkap. Meskipun mahasiswa terbiasa menggunakan teknologi digital, banyak yang belum memiliki keterampilan penelusuran ilmiah yang memadai. Intervensi yang efektif meliputi pelatihan literasi informasi, integrasi dalam kurikulum, dan pembelajaran berbasis simulasi. Literasi digital juga berpengaruh terhadap efikasi diri dan kesehatan mental mahasiswa. Literasi digital dan keterampilan penelusuran literatur perlu diintegrasikan secara sistematis dalam pendidikan kedokteran. Penguatan kurikulum di bidang ini mendukung kesiapan mahasiswa dalam menghadapi tantangan informasi dan teknologi medis.